Assessment of the eating pattern and food choices of high-performance karate athletes in a post-COVID-19 pandemic championship (Research, Society and Development, 2022)
The present study aimed to document the eating pattern and food choices of competitive high-performance karate athletes, during an in-person post-pandemic championship, for discussing adequacy and proposing alternatives to potentiate their performance and recovery in future competitions, respecting the nutritional values. The 47 athletes (57.4% male), of whom 47% had podium award, participated in the study by filling out an electronic anamnesis form and an online 24-hour recall of food intake and choices. The athletes were, on average, 37.0 (9.8) years old and, on the competition day, had a dietary pattern characterized by a normocaloric, low-carbohydrate, normoproteic, high-fiber diet including alcohol intake. Based on the analysis, changes were suggested for energy and macro- and micronutrient intake before, during and after the competition period, maintaining the nutritional values based on scientific evidence for assertive nutritional prescription focused on performance and recovery potentiation after a high-performance competition. This was the first study to perform and document the concomitant evaluation of the eating pattern and food choices during an official karate championship after 2-year suspension of in-person national contests. It was possible to reconcile guidelines to potentiate the performance and recovery in competitions, maintaining and adapting the nutritional values of karate athletes according to the nutritional science.